Mechatronic Design and Development of an Autonomous Mobile Robotics System for Road Mark Painting - Ali, Mohammed A. H.; Musa, Mailah; Wan Azhar, Wan Yusoff; Zamzuri, Hamedon; Zulkifli, Md. Yusof (2016)
this paper presents a mechatronic design and development of a new WMR experimental rig prototype for autonomous road marks painting. The platform includes three main units: differential drive unit, measurement and vision unit and processing unit. The sensors, actuators and the interface free controller cards are connected together in such a way that ensures high performance for exchange the data from the on-board computer to the sensors and actuators. The embedded controller of the proposed platform has been developed to integrate the mechanical components with electronics and software algorithms. The painting system is attached on the WMR platform to perform autonomous on-the-road mark painting. The design, components, control of the paint task and the connection to the main WMR controller are also presented.